Durability of ultra high performance concrete incorporating palm oil clinker as aggregate replacement - Nurul Anis Syafawani, Jabar (2019)
The advancement in the construction industry has promoted the utilization of concrete. Hence, the market for the coarse aggregate is also increased. The increase in demand on the coarse aggregate has led to the depletion of these natural resources thus contributed to the pollution. An alternative to the gravel is required to solve the problem and palm oil clinker is the appropriate substances that can replace the gravel because of its similar properties to the natural aggregate. The durability of the concrete incorporating palm oil clinker was studied in this research and being compared to the durability of the conventional concrete. Furthermore, the suitability of palm oil clinker in the concrete was studied to reduce the reliance of the natural aggregate in the production of concrete. Palm oil clinker concrete is a type of concrete where of the coarse aggregate was replaced by 5%, 10% and 15% of palm oil clinker and produce a new concrete mix. The durability of both of concretes was determined in three durability tests. The tests for durability of the concrete are water absorption test, sorptivity test and water penetration test. The size sample used for the test is 100x100x100 mm. All the cubes samples were cured in the water for 7, 28 and 60 days until it reach the maximum strength. The change in mass and the porosity of the concrete was determined and the durability properties was discussed and being compared. The result shows that the conventional concrete is more durable compared to the concrete incorporate palm oil clinker. In the sorptivity test, conventional concrete has sorptivity value about 0.651 while palm oil clinker concrete was about 0.662. In term of water penetration, more water was penetrated in palm oil concrete compared to the conventional concrete. The durability of the concrete was related to the porosity and permeability of the concrete. From the result, it shows that concrete with have higher porosity is more permeable to the solution and cause matrix destruction. That described that the conventional concrete has better durability than palm oil clinker concrete. Nevertheless, the durability of palm oil clinker is still acceptable and the partial used of the palm oil clinker as coarse aggregate replacement can reduce the dependency of natural resources in the concrete industry.